Manajamen Guru SD Swasta Tafdhil Al Qur’an Padangsidimpuan untuk Menciptakan Metode Pembelajaran Gasing (Gampang, Asyik dan Menyenagkan) - Alfadhili, Muhammad Ro’yi; Hasibuan, Zainal Efendi (IQ (Ilmu Al-qur'an): Jurnal Pendidikan Islam, 2023)
The learning methods that occur in the classroom educators must be able to apply and approach students. The learning process in the classroom takes a lot of time, sometimes it can feel boring or monotonous. The learning process in the classroom takes a lot of time, sometimes it can feel boring or monotonous. This research aims to determine the Management of Padangsidimpuan Tafdhil Al Qur'an Private Elementary School Teachers to Create Gasing (Easy, Fun, Exciting) Learning Methods. The method used in this research is qualitative descriptive analysis. The results obtained from this research are that the top method really helps educators to carry out the learning process and students increase their motivation and interest in the learning process.